Effect Of Mudarabah And Musharakah On Return On Asset (ROA) Islamic Commercial Banks 2015-2019 Period - Ghitha Millatina Islamiyati; Nana Diana (FEB Universitas Sultan Ageng Tirtayasa, 2021)
The function of this research is to disclose how the effect of mudarabah and musharakah on the Return on Asset (ROA) Islamic Commercial Banks 2015-2019 period. The population is all data in the financial statements contained in Islamic Commercial Banks in Indonesia, as many as 14 Islamic banks during period 2015-2019. The method used are descriptive analysis method, multiple regression analysis, partial regression coefficient test (t test) and simultaneous regression coefficient test (F test). The dependent variable (Y) used are Return on Asset (ROA) and variable in the dependent is Mudarabah (X1) and Musharakah (X2). The results showed that partially mudarabah and musharakah did not have a significant effect on Return On Asset (ROA). In simultaneous testing, the results show that mudarabah and musharakah together do not significantly affect the Return On Asset (ROA) of Islamic Commercial Banks in Indonesia for period 2015-2019.